Times of disenchantment: a neoliberal dystopia in the urban apocalypse - de Oliveira, Leandro Dias (Geografares, 2024)
Review of the book The Walking Dead explica a natureza da cidade e o sentido do neoliberalismo, by Tadeu Alencar Arrais (Rio de Janeiro: Letra Capital, 2022, 88p.). Based on an analysis of the famous American series, the author discusses themes such as urbanization, neoliberalism and violence. The Walking Dead is a metaphor for daily life in very difficult times.
Keywords: neoliberalism; urbanization; precariousness; police State; The Walking Dead